Formal Finance and Trade Credit during China's Transition - Cull, Robert (2012)
Using a large panel dataset of Chinese industrial firms, we find that poorly performing SOEs were more likely to redistribute credit to firms with less privileged access to loans via trade credit. While that could be consistent with the efficient redistribution of credit, it is more likely that these SOEs extended trade credit to prop up faltering customers that were in arrears. By contrast, profitable private domestic firms were more likely to extend trade credit than unprofitable ones. Trade credit likely provided a substitute for loans for these firms' customers that were shut out of formal credit markets. As biases in lending become less severe, the allocation of lending became more efficient, and the amount of trade credit extended by private firms declined. Our evidence implies that redistribution of bank loans via trade was not a major contributor to China's explosive growth.